TANTANGAN USAHA PEDAGANG UMKM BAKSO SYAHID - Tatia Hervi Farinka Riyadi; Siti Abibah; Suci Nabila Syahputri; Syaqila Nain Lubis; Zainarti Zainarti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly in absorbing labor and providing employment opportunities for the community. One type of MSME that is growing rapidly in Indonesia is the culinary business, including meatballs. This study aims to analyze the various challenges faced by the Bakso Syahid MSME in running and maintaining its business sustainability. The research method used was a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation. The results indicate that the Bakso Syahid MSME faces several key challenges, including limited business capital, fluctuating raw material prices, increasingly fierce business competition, limited marketing strategies, and obstacles in business management. This research is expected to provide a realistic picture of the condition of culinary MSMEs and serve as a consideration in formulating more sustainable business development strategies.